ANALISIS MARKETING MIX PADA PRODUK INDOMIE DI KOTA BIMA - Sri Ernawati (Jurnal Ilmiah Satyagraha, 2021)
This study aims to determine the product marketing mix of Indomie products in the city of Bima. The type of research used is descriptive, the research location is in the city of Bima. The population in this study are all consumers who have bought Indomie products, the sample in this study amounted to 100 people with a purposive sampling technique. The research instrument used a questionnaire with a Likert scale measurement. The type of data used in this study was quantitative data with the research data source, namely primary data. Data collection techniques are observation, questionnaires and literature study. Data analysis using one sample t test. The results showed that the product marketing mix of Indomie products in Bima City was above the predetermined criteria of 75% (Good)